M = (x₁ + x₂)/2 , (y₁ + y₂)/2
(-1, 2) = ![\frac{3 + x}{2} , \frac{4 + x}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%20%2B%20x%7D%7B2%7D%20%2C%20%5Cfrac%7B4%20%2B%20x%7D%7B2%7D)
At this point, it is easier to separate the x's and y's into two different equations:
x's: -1 =
-2 = 3 + x
-5 = x
y's: 2 = ![\frac{4 + x}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%20%2B%20x%7D%7B2%7D)
4 = 4 + x
0 = x
Answer: (-5, 0)
Answer: ![(x-2)^2 + (y+3)^2 = 36\\\\](https://tex.z-dn.net/?f=%28x-2%29%5E2%20%2B%20%28y%2B3%29%5E2%20%3D%2036%5C%5C%5C%5C)
Work Shown:
![(x-h)^2 + (y-k)^2 = r^2\\\\(x-2)^2 + (y-(-3))^2 = 6^2\\\\(x-2)^2 + (y+3)^2 = 36\\\\](https://tex.z-dn.net/?f=%28x-h%29%5E2%20%2B%20%28y-k%29%5E2%20%3D%20r%5E2%5C%5C%5C%5C%28x-2%29%5E2%20%2B%20%28y-%28-3%29%29%5E2%20%3D%206%5E2%5C%5C%5C%5C%28x-2%29%5E2%20%2B%20%28y%2B3%29%5E2%20%3D%2036%5C%5C%5C%5C)
Note that (h,k) = (2,-3) is the center and r = 6 is the radius. The last line is not expanded out using the FOIL rule because its common practice to leave it in
form. This form allows the reader to quickly determine the center and radius (rather than have to do a lot of algebraic steps before hand).
20% of the juice is cranberry
80% of the juice is apple
Our ratio would be 20:80
We can simplify it and it will become
1:4
So your answer would be B. 1:4
I hope this helps :)
<span>Answer: </span><span>45.2548339959</span>
Answer:
![\bold{h=\dfrac{3Q}{t-r}}](https://tex.z-dn.net/?f=%5Cbold%7Bh%3D%5Cdfrac%7B3Q%7D%7Bt-r%7D%7D)
Step-by-step explanation:
![\bold{r+\frac{3Q}h=t}\\-r\qquad\ -r\\\bold{\frac{3Q}h=t-r}\\\cdot h\qquad \cdot h\\ \bold{3Q=(t-r)h}\\^{\div(t-r)\quad\div(t-r)}\\\bold{\dfrac{3Q}{t-r}=h}](https://tex.z-dn.net/?f=%5Cbold%7Br%2B%5Cfrac%7B3Q%7Dh%3Dt%7D%5C%5C-r%5Cqquad%5C%20-r%5C%5C%5Cbold%7B%5Cfrac%7B3Q%7Dh%3Dt-r%7D%5C%5C%5Ccdot%20h%5Cqquad%20%5Ccdot%20h%5C%5C%20%5Cbold%7B3Q%3D%28t-r%29h%7D%5C%5C%5E%7B%5Cdiv%28t-r%29%5Cquad%5Cdiv%28t-r%29%7D%5C%5C%5Cbold%7B%5Cdfrac%7B3Q%7D%7Bt-r%7D%3Dh%7D)
Or, if you mean (r+3Q)/h=t:
![\bold{\frac{r+3Q}h=t}\\{}\ \ \cdot h\quad\ \cdot h\\\bold{r+3Q=ht}\\{}\ \ \div t\qquad \div t\\\bold{\dfrac{r+3Q}{t}=h}\\\\\bold{h=\dfrac{r+3Q}{t}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cfrac%7Br%2B3Q%7Dh%3Dt%7D%5C%5C%7B%7D%5C%20%5C%20%5Ccdot%20h%5Cquad%5C%20%5Ccdot%20h%5C%5C%5Cbold%7Br%2B3Q%3Dht%7D%5C%5C%7B%7D%5C%20%5C%20%5Cdiv%20t%5Cqquad%20%5Cdiv%20t%5C%5C%5Cbold%7B%5Cdfrac%7Br%2B3Q%7D%7Bt%7D%3Dh%7D%5C%5C%5C%5C%5Cbold%7Bh%3D%5Cdfrac%7Br%2B3Q%7D%7Bt%7D%7D)